Clinical nursing skills & techniques - Perry, Anne Griffin; Potter, Patricia Ann (St. Louis, Missouri : Mosby Elsevier, 2009)
Offers hundreds of full-color illustrations, a nursing process framework, and step-by-step instructions - with rationales for various steps.
Unit 1: Supporting the Client through the Health Care System -- Unit 2: Vital Signs and Physical Assessment -- Unit 3: Infection Control -- Unit 4: Activity and Mobility -- Unit 5: Safety and Comfort -- Unit 6: Hygiene -- Unit 7: Medications -- Unit 8: Oxygenation -- Unit 9: Fluid Balance -- Unit 10: Nutrition -- Unit 11: Elimination -- Unit 12: Care of Surgical Client -- Unit 13: Dressings and Wound Care -- Unit 14: Home Care -- Unit 15: Special Procedures
Includes index.
Keywords: NURSING-- HANDBOOKS, MANUALS, ETC